1940
DOI: 10.1113/jphysiol.1940.sp003815
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diuretics on the osmotic work done and on the efficiency of the isolated kidney of the dog

Abstract: THE external work performed by the kidney is almost entirely represented by the osmotic work done in the formation of urine from plasma.The osmotic work which can be calculated is the theoretical minimum work and is independent of the mechanism of formation of urine. It is perhaps the most significant way of summarizing the functions of the kidney as an excretory organ. The osmotic work plays much the same part in renal physiology as does the mechanical work in muscle physiology; asynchronous contraction of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1940
1940
1989
1989

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In experiments on dogs it was shown by Van Slyke, Rhoads, Miller and Alving (1934) that an increase of the urea output did not increase the oxygen consumption of the kidneys. This was confirmed by Eggleton, Pappenheimer and Winton (1940) who found that even a very considerable augnientation of diuresis, osmotic work, urea excretion and tubular resorbtion of urea were of very little influence on renal blood flow and renal oxygen consumption in dogs. According to these authors the kidney answers the demand for increased work not by increased metabolism but by increased working efficiency.…”
supporting
confidence: 69%
“…In experiments on dogs it was shown by Van Slyke, Rhoads, Miller and Alving (1934) that an increase of the urea output did not increase the oxygen consumption of the kidneys. This was confirmed by Eggleton, Pappenheimer and Winton (1940) who found that even a very considerable augnientation of diuresis, osmotic work, urea excretion and tubular resorbtion of urea were of very little influence on renal blood flow and renal oxygen consumption in dogs. According to these authors the kidney answers the demand for increased work not by increased metabolism but by increased working efficiency.…”
supporting
confidence: 69%
“…This value of 21 mm. may be a few per cent too high for reasons given elsewhere [Eggleton et al 1940b], and our fairest estimate of the change in hydrostatic pressure head across the glomerular membrane equivalent to a change by 1% in serum protein would be 20 mm. Hg in the isolated kidney.…”
Section: Mechanisms Of Dilution Diuresis Resultsmentioning
confidence: 68%
“…The urine flow may be kept constant by variations in ureter pressure (Fig. 6) [Eggleton, Pappenheimer & Winton, 1940b] and this complicates the interpretation of the changes in composition of the urine.…”
Section: Mechanisms Of Dilution Diuresis Resultsmentioning
confidence: 99%
“…Thus Borsook and Winegarden (1931), who set out to calculate in great detail the osmotic work performed by the kidney in producing one litre of urine, came to the conclusion that the total work amounted to 704 gramme calories and that the quota of this due to the calcium ion was only 1 gramme calorie-i.e., about 0.14%. Previous estimates of the total work of the kidney in producing a litre of urine had been of the same order (Cushny, 1926), and the principles and methods of all these authors were accepted as being substantially correct by Eggleton, Pappenheimer, and Winton (1940)..…”
Section: Storage Of Calciummentioning
confidence: 99%